THE INFLUENCE OF QUIPPER SCHOOL LMS ON LEARNING RESULTS OF ARITHMATIC SEQUENCES AND SERIES IN SMA DR. SOETOMO IN THE TIME OF THE COVID-19 PANDEMIC - Ardhi Rizky Maulana; Ninik Mutianingsih (IAIN Ambon, 2021)
This study aims to determine the effect of using LMS Quipper School in online learning on student learning outcomes. This study used samples from two high school classes of DR. Soetomo Surabaya. Each class consists of 31 students. This research was conducted to test the validity, reliability, and hypothesis. From the first result, there were 26 valid questions according to the calculation of Rcount > Rtable worth 0.367. In the hypothesis test there are three stages, namely normality test, homogeneity test, and independent t-test. in normality test, the result of significant value is more than 0.05 so that it is normally distributed. In the homogeneity test, it is known that the Fcount of the two classes is 1.397. It will be searched for Ftable with a standard significance of 5% with df numerator (Between Groups) of 1 and df of denominator (within Groups) of 60, it is known that the result of Ftable is 4.03 so it can be concluded that Fcount≤ Ftable, then H0 is accepted. In hypothesis test, the result of sig.(2-tailed) is 0.002 less than 0.05 so that the hypothesis H0 is rejected. So from this conclusion, there is a significant effect on learning outcomes